Kollektivität Geteilte Autorschaften und kollaborative Praxisformen 1770-1840 - Ehrmann, Daniel (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The paradigm of individual authorship becomes dominant around 1800. It gives way to the notion that literature can be regarded as 'art'. Although this contributes to the success of literature since, it also tends to decrease the visability of the often collaborative practices of writing. This book analyses the crucial role of the connection between individual authorship and collaborative practices.